Frequency of Automatic Stimulations in Responsive Vagal Nerve Stimulation in Patients With Refractory Epilepsy. Issue 6 (24th August 2020) - Kulju, Toni; Haapasalo, Joonas; Verner, Ryan; Dibué‐Adjei, Maxine; Lehtimäki, Kai; Rainesalo, Sirpa; Peltola, Jukka
Abstract: Background: In vagal nerve stimulation (VNS) therapy, the release of VNS model 106 (AspireSR) allowed for responsive VNS (rVNS). rVNS utilizes a cardiac‐based seizure detection algorithm to detect seizure‐induced tachycardia to trigger additional stimulation. There are some studies suggesting clinical benefits of rVNS over traditional VNS, but the performance and significance of autostimulation mode in clinical practice are poorly understood. Objectives: To assess the effect of initiation of rVNS therapy and altered stimulation settings on the number of daily stimulations and energy consumption in VNS therapy and to compare autostimulation performance in different epilepsy types. Materials and Methods: Retrospective follow‐up of 30 patients with drug‐resistant epilepsy treated with rVNS including 17 new implantations and 13 battery replaces at a single center in Finland. Our data consist of 208 different stimulation periods, that is, episodes with defined stimulation settings and both autostimulation and total stimulation performance‐related data along with clinical follow‐up. Results: The variation in autostimulation frequency was highly dependent on the duration of the OFF‐time and autostimulation threshold ( p < 0.05). There was a large additional effect of autostimulation mode on therapy time and energy consumption with longer OFF‐times, but a minor effect with shorter OFF‐times. Significantly more autostimulations were triggered in the temporal lobe and multifocal epilepsies than in extratemporal lobe epilepsies. Conclusions: The initiation of autostimulation mode in VNS therapy increased the total number of stimulations. Shortening the OFF‐time leads to a decreased number and share of automatic activations. Epilepsy type may affect autostimulation activity.